Right, power, and politics? : US-Japan diplomatic encounters in the postwar era - Mauricio, Tiago Alexandre Fernandes (2016)
This paper examines three key moments in the United States-Japan relationship in the postwar period: the US Occupation, between 1945-52; the reversion of Okinawa, in 1972; and the transformation of the alliance in the mid-1990s. It identifies a power-justice nexus that explains Japan’s greater or lesser diplomatic ability to shape its foreign policy vis-à-vis America. This nexus is highlighted in Thucydides’ Melian Dialogue, stressing the underlying tension between right and might in state behaviour. The three case studies take into consideration not only the asymmetric distribution of power but also Japan’s domestic politics, insofar as the latter impacts Tokyo’s diplomatic leverage. By resorting to the founding documents that defined the relationship in these three moments, this study concludes Japan bargained for increasingly more satisfactory arrangements. Japan thus shifted from a position of client state to junior partner in a global alliance. These case studies further demonstrate the impact of the relative power distribution in Japan’s diplomatic efforts, emphasizing external constraints on its foreign policy decision-making.